Nurses' experiences of self-management support for adults with tuberculosis and human immunodeficiency virus coinfection - Eric Tornu; Portia J. Jordan; Michael McCaul (AOSIS, 2024)
Background: Professional nurses provide self-management support to adults (18 years and older) living with tuberculosis (TB) and human immunodeficiency virus (HIV) coinfection to enable them to mitigate its impact on their lives. However, the experiences of professional nurses providing self-management support to adults with TB-HIV coinfection remain unclear. Aim: This study explored and described the experiences of professional nurses on the provision of self-management support to adults living with TB-HIV coinfection in Greater Accra, Ghana. Setting: Three public primary health facilities in Greater Accra, Ghana. Methods: An exploratory, descriptive qualitative design was used. Twenty-two purposively sampled professional nurses were interviewed face-to-face individually using an interview guide. Interviews were recorded with participants' permission, transcribed and analysed thematically using MAXQDA software. Results: The three themes generated revealed that the: (1) self-management problems of adults living with TB-HIV coinfection included their recurring physical, mental and social problems, (2) the support provided to adults with TB-HIV coinfection included symptom, nutritional, medication and psychosocial self-management support, (3) the factors related to providing self-management support showed that self-management support was influenced by patient, nurse and health facility-related factors but was feasible, equitable and acceptable to patients and stakeholders. Conclusion: Professional nurses' self-management support practice entailed improvising limited resources to address the recurring problems of adults living with TB-HIV coinfection. Nurses require adequate resources to provide comprehensive self-management support. Contribution: The contextual evidence provides insight into the self-management problems of adults with TB-HIV coinfection and the factors influencing professional nurses' self-management support.